2021
DOI: 10.3389/fimmu.2021.657211
|View full text |Cite
|
Sign up to set email alerts
|

Lower IgA Levels in Chronic Spontaneous Urticaria Are Associated With Lower IgE Levels and Autoimmunity

Abstract: BackgroundThe pathogenesis of chronic spontaneous urticaria (CSU) is still insufficiently understood. Recent findings suggest that immunoglobulins, in particular IgE but also IgA, play a role in the development of CSU.ObjectiveOur aim was to assess differences in clinical and laboratory markers between CSU patients with and without lower levels of serum IgA and IgE.MethodsWe analyzed the data of 606 patients with CSU by dividing them into four groups based on their IgA and IgE levels. The groups were compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
5
9
0
Order By: Relevance
“…Our findings are consistent with the results of a previous study which has shown that lower tIgE is associated with higher prevalence rates of anti-TPO IgE. 12 The antihistamine-refractory CSU patients with positive anti-TPO IgE can be successfully treated with omalizumab. 16 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the results of a previous study which has shown that lower tIgE is associated with higher prevalence rates of anti-TPO IgE. 12 The antihistamine-refractory CSU patients with positive anti-TPO IgE can be successfully treated with omalizumab. 16 …”
Section: Discussionsupporting
confidence: 92%
“…In this large-sample-size study, we have confirmed higher prevalence rates of anti-TPO IgE and anti-TG IgE in a Chinese Han CSU population and significant correlation between the prevalence rates of anti-TPO IgE and anti-TPO IgG. In line with Sauer et al ’s study, 12 we found that the elevated prevalence rates of anti-TPO IgE were associated with lower tIgE levels. The elevated levels of anti-TG IgE in patients with severe CSU decrease after omalizumab treatment.…”
Section: Discussionsupporting
confidence: 90%
“…According to previous studies ASST is considered as a bedside clinical test which can detect the presence of autoimmunity in patients with CSU. 1,21,23,24 Our results agreed with a study, reported that 56% of CSU patients had negative ASST, and pointed out to lack of functional circulating autoantibodies in these patients. 25 However, since 44% of their patients had positive ASST, they suggested that this observation may indicate the presence of functional circulating autoantibodies and an autoimmune basis for their disease.…”
Section: Discussionsupporting
confidence: 92%
“…The BAT is positive if healthy donor basophils degranulate due to autoantibodies present in the patients’ serum. The BAT was performed as previously described ( 4 ). Briefly, the patient’s serum was thawed and incubated with fresh basophils taken from a healthy donor.…”
Section: Methodsmentioning
confidence: 99%
“…In CSU, total immunoglobulin E (IgE) levels have been found to be elevated in a large proportion of patients (2,3) and it is thought to play an important role in the pathogenesis of CSU. Despite this, there are some patients who present with low or very low levels of total IgE (4,5). These patients are especially difficult to treat and are more often non-responders to treatment with Omalizumab, a therapeutic anti-IgE antibody, than those with normal or elevated total IgE (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%